Pengaruh PKB dan Harga terhadap Daya Beli Mobil di Kota Surabaya - Reza Duta Apriliyanto; Lis Setyowati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to determine the effect of vehicle tax and price on the purchasing power of four-wheeled vehicles in the city of Surabaya. This type of research uses quantitative research. This study uses primary data and secondary data. The sampling technique used in this study is probability / random sampling technique using the slovin formula, so that the number of samples in this study is 100 respondents. The results of this study indicate that vehicle taxes and prices have an effect on the purchasing power of four-wheeled vehicles in the Surabaya city area, vehicle taxes and prices have a simultaneous effect on the purchasing power of four-wheeled vehicles in the Surabaya city area with R square values of 62.9% and 37.1 % influenced by other variables.